Pathogenicity and transmission of fungi detected on Passiflora alata seeds - Parisi, João José (2018)
Passion fruit is usually propagated by seeds because of the ease and lower cost in seedling production. However, the seed is the most efficient agent for the spread of pathogens. The damages from seed-borne diseases occur mainly during the germination stages or at the formation of seedlings in nurseries. Considering the need for knowledge on the pathology of sweet passion fruit seeds, the objective was to evaluate the transmission and pathogenicity of the fungi Alternaria sp., Botrytis fabae, Cladosporium cladosporioides, Fusarium spp. and Lasiodiplodia theobromae, known as potentially pathogenic to this crop, and isolated from sweet passion fruit seeds. Therefore, tests on seed health, germination and seedling emergence in a sterilized commercial substrate were conducted using seeds from this species, inoculated with those fungal isolates. Leaves, stems and fruit from this plant were also inoculated with the same fungi. Alternaria sp., Fusarium spp. and L. theobromae were identified in seedlings obtained from inoculated seeds, confirming the transmission of these fungi by seeds. L. theobromae was also considered the most harmful fungus to passion fruit crop, as it causes seed rot and other disease symptoms on the leaves, stem and fruit. These findings inferred that healthy seeds of sweet passion fruit are essential for producing seedlings and to prevent the spread of the diseases caused by these fungi to exempt areas.